THE PRICING MODEL FOR SHARED APPRECIATION MORTGAGE AND RELATED FACTORS - SHI, YI (2007)
Abstract As one of new equity convertible mortgage, the Shared-Appreciation Mortgage, which is the recent rise in financial market and motivates careful consideration of underlying borrower incentives. The SAM borrower will give up the fractional share of the house appreciation in exchange of a lower payment rate on mortgage. In this paper, based on the previous literary study on the pricing techniques, we go through the paper about the conventional Fixed-rate mortgage: the KKME Model initially and some other related development from that model with the embedded options like prepayment and default option. Furthermore, some papers also provide some creative ideas to facility the progress of the pricing model of shared appreciation mortgage. Especially on this paper, there is some new idea about dividing the SAM calculation into two parts: Credit Facility and Valuation of Mortgage. The first part is used to evaluate the equilibrium contract rate for the SAM mortgage contract. The second part is to apply the binominal tree method to evaluate the value of prepayment and default option in order to get the final value of SAM. This paper also analyse on the relationship between SAM and some related factors which may influence the contract rate or the value of options, e.g. the moral hazard, appraisal error.